Cryotherapy is effective in nulliparous women with primary dysmenorrhea: a randomized controlled trial - Pérez Domínguez, Borja; González-Ruiz, Lucía; Muñoz-Ibáñez, Sara; Blanco-Diaz, María; Díaz-Mohedo, Esther (Mary Ann Liebert, 2025)
Primary dysmenorrhea is a prevalent condition causing severe menstrual pain in nulliparous women, negatively impacting daily functioning and well-being. This randomized controlled trial investigated the efficacy of cryotherapy in alleviating pain and enhancing secondary outcomes such as sleep quality, quality of life, and physical activity. Fifty-eight nulliparous women were randomly assigned to a cryotherapy group or a control group. Pain intensity was measured using the Numeric Rating Scale, whereas secondary outcomes were evaluated with the Pittsburgh Sleep Quality Index, World Health Organization Quality of Life-Brief Version, and the International Physical Activity Questionnaire. Socioeconomic factors, including household income, education, and occupation, were also assessed. Cryotherapy significantly reduced pain intensity from a baseline of 7.1 ± 1.4 to 1.8 ± 1.7 (p < 0.001) compared with a modest reduction in the control group (5.9 ± 1.9-5.4 ± 2.1). Sleep quality improved more in the cryotherapy group (6.90 ± 3.0 to 5.03 ± 2.5) than in the control group (6.88 ± 3.6 to 5.68 ± 2.8). However, no statistically significant changes were observed in the quality of life or physical activity levels, likely because menstrual pain alone may not sufficiently influence these domains, which are affected by broader psychosocial and behavioral factors. These findings demonstrate that cryotherapy is a simple, cost-effective intervention for managing primary dysmenorrhea, providing substantial pain relief and modest improvements in sleep quality. Further research is recommended to evaluate its long-term benefits and potential for broader applications in menstrual health management.
https://openpolicyfinder.jisc.ac.uk/id/publication/1477
Keywords: Dismenorrea - Tratamiento; Menstruación - Trastornos; Crioterapia; Cryotherapy; Dysmenorrhea; Menstrual pain; Pain management; Physical therapy modalities; Primary; Randomized controlled trial